The volatile profile for discrimination of lavender and heather honey, using solid phase microextraction and gas chromatography-mass spectrometry - Falcão, Soraia (2018)
Honey is a natural product produced by Apis mellifera bees from the nectar or secretions of plants, which has a long history of human consumption. It is also used in various foods and beverages as a sweetener and flavouring. The main parameters of honey quality, which also influence its price, are derived from its botanical origin. Honey volatiles have been used as markers for its authenticity. They may arise from the nectar source, from the transformation of plant compounds by the honeybee, directly generated by honeybee, from heating or handling during honey processing and storage or from microbial or environmental contamination [1]. The aim of this work is the discrimination of monofloral Lavandula spp. and Erica spp. honeys through its volatile profile. For that, eighteen samples from both lavender and heather honey, were analyzed. Volatiles were sampled by headspace solid phase microextraction (HS-SPME) using a 65 μm polydimethylsiloxane divinylbenzene (PDMS/DVB) fiber. The chemical identification was performed by gas chromatographymass spectrometry (GC-MS). A complex total ion chromatogram was obtained, with nearly seventy compounds identified and quantified. The aldehydes and terpenic derivatives were the most likely to relate honey to its floral origin, being phenylacetaldehyde and nonanal the most representative in lavender honey while hotrienol was the most abundant in the heather honeys. The above methodology was suitable for the isolation of low-molecular-weight aroma compounds, particularly for the short-chain aliphatic compounds that are important for authentication of lavender and heather honey.